2013
DOI: 10.1037/a0032141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of job crafting on job demands, job resources, and well-being.

Abstract: This longitudinal study examined whether employees can impact their own well-being by crafting their job demands and resources. Based on the job demands-resources model, we hypothesized that employee job crafting would have an impact on work engagement, job satisfaction, and burnout through changes in job demands and job resources. Data was collected in a chemical plant at three time points with one month in between the measurement waves (N = 288). The results of structural equation modeling showed that employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
866
7
25

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 868 publications
(1,035 citation statements)
references
References 52 publications
57
866
7
25
Order By: Relevance
“…The findings of this study demonstrate the relationship between both daily seeking challenges and seeking resources and daily work engagement. Contrary to expectation, yet similar to Tims et al (2013), no relationship was found between reducing demands and work engagement. Mean levels of day-level reducing demands were the highest of all crafting dimensions (4.39), demonstrating that employees reduced their job demands on a daily basis.…”
Section: Resourcescontrasting
confidence: 51%
See 4 more Smart Citations
“…The findings of this study demonstrate the relationship between both daily seeking challenges and seeking resources and daily work engagement. Contrary to expectation, yet similar to Tims et al (2013), no relationship was found between reducing demands and work engagement. Mean levels of day-level reducing demands were the highest of all crafting dimensions (4.39), demonstrating that employees reduced their job demands on a daily basis.…”
Section: Resourcescontrasting
confidence: 51%
“…autonomy) and social (e.g. support) resources over a two month period (Tims, Bakker & Derks, 2013). Similarly Leana and colleagues found that work discretion was positively related to individual job crafting for teachers and their aides (Leana, Appelbaum & Shevchuk, 2009).…”
Section: Question 4: How Does the Interplay Of Job Resources And Jobmentioning
confidence: 99%
See 3 more Smart Citations